Kreativitas Guru Pendidikan Agama Islam dalam Meningkatkan Mutu Pembelajaran - Fathorrahman Fathorrahman (Universitas Al-Amien Prenduan, 2018)
Teacher's creativity is indispensable as an effort to produce a good quality of education. Islamic Education has potential monotheism and the creed of the individual, because it is a model of learning and exemplary Qur'ani that should really understand Islamic education teachers. For this reason this study was conducted in order to determine the extent to which Islamic religious education teacher creativity in improving the quality of student learning in Madrasah Aliyah Al-Amien I Puteri Prenduan, This research was descriptive qualitative approach. Sources of data obtained through observation, interviews and documentation. Data Subject was the principal, teachers and some students featured PAI. Data analysis techniques used inductive-way interpretation of the processed data through checking and organizing techniques. The results of field research showed that: First, the lesson of Islamic religious education in MA Al-Amien I Puteri Prenduan been done correctly and well, this was evidenced by teacher preparation prior to the learning process. Secondly, there was the attempt PAI teacher creativity in improving the quality of learning of them involving students actively summarize any given subject, knowing how to write and read the Quran and evaluated gradually learning from each material. Third, the quality of student learning featured PAI couldbe said to be satisfying. Conclusions showed that the apparent from the evidence: the creation of a harmonious relationship between teachers and students, private Forming superior Muslim faith, piety and charitable pious and achievement of learning goals of Islam with the average value of students featured, above a value of 75 (predicate B).